The great crisis and the American response - James K. Galbraith (Levy Economics Institute of Bard College, 2010)
Senior Scholar James K. Galbraith argues the fundamental illusion of viewing the US economy through the free-market prism of deregulation, privatization, and a benevolent government operating mainly through monetary stabilization - the prevailing view among economists over the past three decades. The real sources of American economic power, he says, lie with those who manage and control the public-private sectors - especially the public institutions in those sectors - and who often have a political agenda in hand. Galbraith calls this the predator state: a government that is intent, not upon restructuring the rules in any idealistic way, but upon using the existing institutions as a device for political patronage on a grand scale. And it is closely aligned with financial deregulation.
Keywords: 330; Finanzmarktkrise; Konjunkturpolitik; Geldpolitik; Finanzsektor; Bankenpolitik; Internationaler Finanzmarkt; USA; Welt